Stereoselective C-3 alkylation of trans-3-phenylsulfonyl-β-lactams with organic halides to access C-3 substituted β-lactams using sulfonyl moiety as an activating group. Issue 29 (16th July 2020) - Bhalla, Aman; Modi, Garima; Yadav, Pooja; Kumar, Pankaj; Bari, S.S.; Hundal, Geeta
Graphical abstract: Highlights: Sulfonyl group activate C-3 alkylation of trans- 3-phenylsulfonyl-β-lactams. Mild reaction conditions, cost effective and functional group tolerance. Exploration of steric bulk on C-3 alkylation of β-lactams. Stereoselective synthesis of cis- +/or trans- alkyl-β-lactams with organic halides. Stereochemistry at C -3 of β-lactam 7d was confirmed by X-ray structural analysis. Abstract: A sulfonyl promoted synthetic protocol for the C-3 alkylation of trans -3-phenylsulfonyl-β-lactams 6(a-e) with active organic halides in presence of K2 CO3 as mild base and DMF as solvent is described. This protocol furnished cis- and trans -β-lactams as major and minor isomers respectively with alkyl halides while arylalkyl/unsaturated halides yield only cis -β-lactams exclusively. Further, the effect of sterically bulky group on the C-3 substitution was investigated by the reaction of 3-phenylsulfonyl-β-lactams 6(d-e) with crotyl chloride (predominantly E ) to achieve diastereomeric mixture of β-lactams 7/7ʹ and 8 . This strategy reveals advantages in terms of cost effectiveness, functional group tolerance and ease of operation.